Managing lenticel browning in mango— the farmer-friendly way - Sharma, R R; Prasad, K (Indian Horticulture, 2019)
The lenticels are macroscopic porous openings, consisting of cells with large intercellular spaces in the periderm of secondarily thickened organs, especially fruits of mango. These openings play significant role in transpiration and exchange of gases. Lenticels act as a necessary evil as they are required for several physiological functions in the plant, but their discoloration leads to the loss in quality, and thus it is considered as one of the main problems in post-harvest management of mango. Lenticel browning has been reported to be serious post-harvest problem in mango.